Manganese-driven CoQ deficiency - Diessl, Jutta; Berndtsson, Jens; Broeskamp, Filomena; Habernig, Lukas; Kohler, Verena; Vazquez-Calvo, Carmela; Nandy, Arpita; Peselj, Carlotta; Drobysheva, Sofia; Pelosi, Ludovic; Vögtle, Friederike-Nora; Pierrel, Fabien; et al. (Nature Communications, 2022)
Overexposure to manganese disrupts cellular energy metabolism across species, but the molecular mechanism underlying manganese toxicity remains enigmatic. Here, we report that excess cellular manganese selectively disrupts coenzyme Q (CoQ) biosynthesis, resulting in failure of mitochondrial bioenergetics. While respiratory chain complexes remain intact, the lack of CoQ as lipophilic electron carrier precludes oxidative phosphorylation and leads to premature cell and organismal death. At a molecular level, manganese overload causes mismetallation and proteolytic degradation of Coq7, a diiron hydroxylase that catalyzes the penultimate step in CoQ biosynthesis. Coq7 overexpression or supplementation with a CoQ headgroup analog that bypasses Coq7 function fully corrects electron transport, thus restoring respiration and viability. We uncover a unique sensitivity of a diiron enzyme to mismetallation and define the molecular mechanism for manganese-induced bioenergetic failure that is conserved across species.